2019
DOI: 10.1016/j.redox.2018.101087
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying changes in the bacterial thiol redox proteome during host-pathogen interaction

Abstract: Phagocyte-derived production of a complex mixture of different oxidants is a major mechanism of the host defense against microbial intruders. On the protein level, a major target of these oxidants is the thiol group of the amino acid cysteine in proteins. Oxidation of thiol groups is a widespread regulatory post-translational protein modification. It is used by bacteria to respond to and to overcome oxidative stress. Numerous redox proteomic studies have shown that protein thiols in bacteria, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 70 publications
3
28
1
Order By: Relevance
“…This result suggests that at least with PsA other oxidation products of cysteine residues must be favored over glutathionylation. In contrast to our result, Xie et al (60) recently reported substantial reversible protein thiol oxidation in E. coli phagocytosed by a neutrophil-like cell line. This reversible thiol oxidation may have involved glutathionylation because GSH levels in E. coli are much higher than PsA (27,56).…”
Section: Oxidation Of Bacterial Gsh During Neutrophil Phagocytosiscontrasting
confidence: 99%
“…This result suggests that at least with PsA other oxidation products of cysteine residues must be favored over glutathionylation. In contrast to our result, Xie et al (60) recently reported substantial reversible protein thiol oxidation in E. coli phagocytosed by a neutrophil-like cell line. This reversible thiol oxidation may have involved glutathionylation because GSH levels in E. coli are much higher than PsA (27,56).…”
Section: Oxidation Of Bacterial Gsh During Neutrophil Phagocytosiscontrasting
confidence: 99%
“…Subsequently, we used iodoTMT reporter ion intensities to calculate the average percentage change of oxidation for each peptide. The overall distribution of the thiol oxidation states under both conditions was found notably similar and in accordance with results from other cell types (21,67). In both the stimulated and unstimulated CD4 + T cells, 92% of the characterized cysteine residues were found predominantly reduced with an oxidation status of less than 30%, with the majority residing in the 0-10% oxidation range ( Figures 3A & 3B).…”
Section: Mtros-generating Cd4 + T Cells Maintain Their Overall Thiol supporting
confidence: 86%
“…Generally, there was only moderate inter-sample deviation of the same conditions between different donors (Supplementary Figure 5). It is well known that the majority of cysteine residues in proteins exist as either significantly oxidized or significantly reduced (67). The oxidation state reflects the overall thiol redox homeostasis of the compartment, with cytosolic proteins having mostly reduced cysteine residues, and conversely, extracellular proteins typically contain structural disulfide bonds.…”
Section: Mtros-generating Cd4 + T Cells Maintain Their Overall Thiol mentioning
confidence: 99%
“…HOCl production by phagocytic cells is one of the central mechanisms to protect host organisms from pathogenic bacteria, including E. coli and P. aeruginosa [32][33][34] . In turn, bacteria have to deal with this intense oxidative insult, with the involvement of Cys-based proteins [35][36][37].…”
Section: Discussionmentioning
confidence: 99%